KONSEP PENDIDIKAN ISLAM DALAM SUNNAH NABI DAN RELEVANSINYA BAGI PEMBELAJARAN PAI DI PENDIDIKAN DASAR - Auliya`, Hilyatul; Mukaffa, Zumrotul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the importance of Islamic education in shaping students’ character, as well as the gap between educational concepts in the Sunnah and the practice of Islamic Religious Education (IRE) in elementary schools, which still tends to be cognitive. The main issues of this study are the educational concepts in the Sunnah, the current state of IRE in elementary education, and their relevance in the context of modern education. This study employs a qualitative approach using library research, through documentation and content analysis of hadith, Islamic educational literature, and previous studies. The results indicate that education in the Sunnah is oriented toward character development through the principles of exemplary behavior, dialogue, experiential learning, gradual progression, and individualization. Meanwhile, PAI instruction in elementary schools still faces various challenges, such as the dominance of the cognitive approach and a lack of value internalization. This study concludes that the concept of education in As-Sunnah is relevant to PAI instruction; however, it requires reinterpretation and contextual adaptation to be effectively applied within the modern education system.